Taʿlīm al-Lughah al-ʿArabiyyah fī Mandhūr Thalāthah Arkān Filsafat al-ʿIlm (al-Anṭūlūjiyā, wa-al-Ibistimūlūjiyā, wa-al-Aksiyūlūjiyā): Teaching the Arabic Language from the Perspective of the Three Pillars of the Philosophy of Science (Ontology, Epistemology, and Axiology) - Hermawan, Dendy (Critical Review of English-Arabic World Journal, 2025)
الفلسفة العلمية هي جزء أصيل في تعليم اللغة العربية، وفهمها يُعَدّ من الضروريات في ميدان التربية من أجل تدريب الطالب على التفكير النقدي في اللغة العربية التي يدرسها. يهدف هذا البحث إلى استكشاف تعليم اللغة العربية في ضوء فلسفة العلم، وذلك من خلال ربطه بثلاثة أركان رئيسة في فلسفة العلم، وهي: الأنطولوجيا، والإبستمولوجيا، والأكسيولوجيا.أما المنهج المتَّبع في هذا البحث فهو البحث المكتبي (الدراسات المكتبية) بالمنهج الوصفي الكيفي. وقد تبيَّن أنَّ في جانب الأنطولوجيا، تعليم اللغة العربية هو دراسة تربوية تبحث في علوم اللغة العربية، وكذلك في اللسانيات العامة مثل النحو، والصرف، وعلم الأصوات، والدلالة. وأما من الجانب الإبستمولوجي، فهو متعلق بكيفية اكتساب الصورة العلمية في اللغة العربية ذاتها، ويشمل التفسير والجوانب الديناميكية، إضافة إلى الأسس المنهجية والنظامية. وفيما يخص جانب الأكسيولوجيا، فهو مرتبط بالقيم في علم اللغة العربية، أي بالعلم اللغوي الذي يُسخَّر لخدمة مصلحة الإنسان. وهذه الأركان الثلاثة للفلسفة تُشكِّل وحدة أساسية ملازمة لكل علم، ولا سيما في تعليم اللغة العربية. The philosophy of science is an essential part of teaching the Arabic language, and understanding it is considered a necessity in the field of education to train students in critical thinking about the Arabic language they study. This research aims to explore Arabic language teaching in light of the philosophy of science by connecting it to the three main pillars of the philosophy of science: ontology, epistemology, and axiology. The method used in this study is library research (desk research) with a qualitative descriptive approach. It was found that, from the ontological perspective, teaching Arabic is an educational study that examines the sciences of the Arabic language, as well as general linguistics, such as grammar, morphology, phonology, and semantics. From the epistemological perspective, it relates to how scientific knowledge of the Arabic language itself is acquired, including interpretation, dynamic aspects, and methodological and systematic foundations. Regarding the axiological perspective, it is related to values in Arabic linguistics, meaning linguistic knowledge that is utilized to serve human interests. These three pillars of philosophy form an essential and inseparable unity for every science, particularly in the teaching of the Arabic language.